The Central Role of Satisfaction in Shaping Customer Loyalty: Insights from Omni-Channel Retailing - Yunita, Dessy; Nofiawaty; Maulana, Ahmad; Malinda, Shelfi (Faculty of Economics and Business, Universitas Negeri Yogyakarta in collaboration with the Institute for, 2025)
The purpose of this study is to determine whether satisfaction mediates the relationship between omni-channel intensity and shopping value on customer loyalty in omni-channel retail. This study focuses on omni-channel customers in Palembang, where data were collected through questionnaires distributed to 200 respondents who had made purchases on at least two retail channels. Data analysis was conducted using AMOS. The findings reveal that omni-channel intensity and shopping value do not directly influence customer loyalty. However, mediation tests show that omni-channel intensity affects customer loyalty through satisfaction, as does shopping value through satisfaction. The study implies that fostering satisfaction in omni-channel retail significantly enhances customer loyalty. To achieve this, it is important to prioritize factors that ensure consistency and seamless channel integration, and the creation of shopping experiences that shape value.